Factors that affect acceptance and use of information systems within the Maritime industry in developing countries: The case of Ghana - Wiafe, Isaac; Koranteng, Felix Nti; Tettey, Thomasina; Kastriku, Ferdinand A.; Abdulai, Jamal-Deen (Journal of systems and information technology, 2020)
PurposeAlthough information and communication technology has become a significant driver for organizational efficiency and effectiveness, there is inadequate empirical research on technology acceptance in the maritime industry especially in developing countries. Literature on how behavior and attitude influence technology acceptance is non-existent. This study therefore aims to augment existing literature on technology acceptance in developing countries with particular emphasis on the maritime industry.Design/methodology/approachThe study extended the unified theory of acceptance and use of technology (UTAUT) model to investigate the factors that affect the acceptance and use of INTTRA: a multi-carrier booking and shipping system designed to facilitate ocean trade worldwide. Responses from 198 subjects, collected through a questionnaire, were analyzed using partial least square structural equation modeling.FindingsThe research model confirmed significant influences of performance expectancy, facilitating conditions, anxiety and attitude towards use on users’ intention to use INTTRA. In contrast, social influence, effort expectancy and self-efficacy did not significantly influence intention to use. Although these findings confirm some proposed relationships in the UTAUT model, it contradicted the cultural dimension argument that developing countries with higher degrees of femininity pay less attention to performance and high attention to social influence.Research limitations/implicationsThe study contributes to knowledge in the area of information systems and technology acceptance in developing countries. Particularly, it seeks to expand literature on adoption within the maritime industry. The study is limited to the sample used for the study, as it used participants from only one country. However, the findings are not generalized for the entire maritime industry but rather Ghana.Originality/valueThe originality of the study is derived from the provision of literature on adoption within the maritime industry in developing countries. It also provided evidence that challenges existing knowledge on characteristics of countries that exhibits high level of femininity culture as proposed by Hofstede.